Early Levallois core technology between Marine Isotope Stage 12 and 9 in Western Europe. Issue 139 (February 2020) - Moncel, Marie-Hélène; Ashton, Nick; Arzarello, Marta; Fontana, Federica; Lamotte, Agnès; Scott, Beccy; Muttillo, Brunella; Berruti, Gabriele; Nenzioni, Gabriele; Tuffreau, Alain; Peretto, Carlo
Abstract: Early Levallois core technology is usually dated in Europe to the end of Marine Isotope Stage (MIS) 9 and particularly from the beginning of MIS 8 to MIS 6. This technology is considered as one of the markers of the transition from lower to Middle Paleolithic or from Mode 2 to Mode 3. Recent discoveries show that some lithic innovations actually appeared earlier in western Europe, from MIS 12 to MIS 9, contemporaneous with changes in subsistence strategies and the first appearance of early Neanderthal anatomical features. Among these discoveries, there is the iconic Levallois core technology. A selection of well-dated assemblages in the United Kingdom, France, and Italy dated from MIS 12 to 9, which include both cores and flakes with Levallois features, has been described and compared with the aim of characterizing this technology. The conclusion supports the interpretation that several technical features may be attributed to a Levallois technology similar to those observed in younger Middle Paleolithic sites, distinct from the main associated core technologies in each level. Some features in the sample of sites suggest a gradual transformation of existing core technologies. The small evidence of Levallois could indicate occasional local innovations from different technological backgrounds and would explain the diversity of Levallois methods that is observed from MIS 12. The technological roots of Levallois technology in the Middle Pleistocene would suggest a multiregional origin and diffusion in Europe and early evidence of regionalization of local traditions through Europe from MIS 12 to 9. The relationships of Levallois technology with new needs and behaviors are discussed, such as flake preference, functional reasons related to hunting and hafting, an increase in the use of mental templates in European populations, and changes in the structure of hominin groups adapting to climatic and environmental changes.